Plan parcial de renovación urbana sobre el río Chipalo y quebrada san Antonio comuna 6 Ibagué - Tolima (2021)
The partial renovation plans are those mechanisms of land management, which are used to improve a critical point within a city, in this matter improve public space, its infrastructure and road morphology, physical and land uses in the sector from commune 6 specifically at the intersection between the Chipalo river and the San Antonio stream and its surrounding neighborhoods. In chapter I, it corresponds to the investigative stage, framing the problems, the research questions and defining the general objective together with the specific ones for the elaboration of the project, the justification and the scope and limitations found within the investigation and execution of the project. In chapter II defines the methodological design used when preparing the research, defining the types of studies carried out and the population involved in the project. In chapter III all the theoretical, conceptual, historical, legal and operational frameworks are defined in which all the urban analysis and diagnosis is developed at different macro and micro scales, defining as such the urban proposal in response to the problems in terms of to the public space to the irregular urban morphology continuity in its road infrastructure. In chapter IV defines the conclusions found throughout the investigation and establishes the recommendations for said interventions on this issue of recovery in public space and the recovery of environmental axes such as the Chípalo River and the San Antonio stream.